2018
DOI: 10.1083/jcb.201707075
|View full text |Cite
|
Sign up to set email alerts
|

Active and inactive β1 integrins segregate into distinct nanoclusters in focal adhesions

Abstract: Through two superresolution microscopy techniques, STED and STORM, Spiess et al. visualize the organization of integrins in focal adhesions and show that active and inactive β1 integrins assemble into distinct nanoclusters within adhesions, suggesting the existence of a novel mechanism that locally coordinates integrin activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 63 publications
11
72
0
Order By: Relevance
“…In particular, β5-integrin was found to assemble high-density ring-like clustering at the edges of adhesions while β1 or αV-integrins were found to be more homogeneously distributed. Within classical focal adhesion, distinct integrin heterodimers display different dynamics (Rossier et al, 2012) or cluster differently depending on their activation states (Spiess et al, 2018). However, the spatial segregation of specific integrin heterodimers appears to be a unique feature of cornerstone adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, β5-integrin was found to assemble high-density ring-like clustering at the edges of adhesions while β1 or αV-integrins were found to be more homogeneously distributed. Within classical focal adhesion, distinct integrin heterodimers display different dynamics (Rossier et al, 2012) or cluster differently depending on their activation states (Spiess et al, 2018). However, the spatial segregation of specific integrin heterodimers appears to be a unique feature of cornerstone adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulating the Integrin b1/FAK/ERK Signaling and Subsequent Matrix Metalloproteinase (MMP)-9 Expression To further unravel the mechanism underlying PKM2-promoted cell invasiveness, we detected the activity of integrin b1 and its downstream signaling. The influence of secreted PKM2 on integrin b1 was investigated using the antibody 12G10, which specifically recognizes the active conformation of integrin b1 (Spiess et al, 2018). Obviously, r-PKM2 induced the activation of integrin b1, without affecting total integrin b1 level ( Figures 6A-6C).…”
Section: Secreted Pkm2 Exerts the Pro-metastasis Function Bymentioning
confidence: 99%
“…To determine if the GIV•K2 interaction persists later in mature FAs, we used two-color super-resolution stimulated emission depletion (STED) microscopy (Hell and Wichmann, 1994;Klar et al, 2000) enabling a lateral resolution of ~40 nm to assess nanoscale colocalization of endogenous pYGIV and K2 within focal adhesions. Prior studies using STED (Colin-York et al, 2017;Spiess et al, 2018) have revealed the superiority of this approach over conventional microscopy for assessing the organization of FAs into nanometer size clusters of multi-protein assemblies. We observed nanoscale co-localization between pYGIV and K2 within mature FA-structures that were positive for paxillin [ Fig 5B]; compared to GIV-WT cells, such structures were far fewer and virtually lacking in cells expressing the PGxA mutant.…”
Section: The Giv•kindlin-2 Interaction Enhances Tumor Cell Adhesion mentioning
confidence: 99%